Preparation of TiO2/SnO2 Thin Films by Sol-Gel Method and Periodic B3LYP Simulations - Floriano, Emerson A. [UNESP]; Scalvi, Luis Vicente de Andrade [UNESP]; Saeki, Margarida Juri [UNESP]; Sambrano, Julio Ricardo [UNESP] (Amer Chemical Soc, 2014)
Titanium dioxide (TiO2) thin films are grown by the sol-gel dip-coating technique, in conjunction with SnO2 in the form of a heterostructure. It was found that the crystalline structure of the most internal layer (TiO2) depends on the thermal annealing temperature and the substrate type. Films deposited on glass substrate submitted to thermal annealing until 550 degrees C present anatase structure, whereas films deposited on quartz substrate transform to rutile structure at much higher temperatures, close to 1000 degrees C, unlike powder samples where the phase transition takes place at about 780 degrees C. When structured as rutile, the oxide semiconductors TiO2/SnO2 have very dose lattice parameters, making the heterostructure assembling easier. The SnO2 and TiO2 have their electronic properties evaluated by first-principles calculations by means of DFT/B3LYP. Taking into account the calculated band structure diagram of these materials, the TiO2/SnO2 heterostructure is qualitatively investigated and proposed to increase the detection efficiency as gas sensors. This efficiency can be further improved by doping the SnO2 layer with Sb atoms. This assembly may be also useful in photoelectrocatalysis processes.